Clustering and aggregation in economics - Fisher, Walter Dummer (Baltimore : Johns Hopkins Press, 1969)
In this study, the author recommends specific simplification procedures to the researcher. He emphasizes the development of a criterion for judging alternative procedures and specific procedures for selecting a good grouping in terms of criterion. The author develops an optimal theory of clustering and aggregation which is applied to three basic types of economic problems: reduced form, input-output, and linear programming. Numerical data are used to determine and illustrate solutions in the form of near-optimal groupings. A step-wise clustering procedure, with brief descriptions of computational programs, is presented.
Includes bibliographical references: p. 139-147.
rpm 22/09/2017
Loans
Keywords: Econometrics